Allocation For Wi-Fi Devices At Campus of Udayana University in Bukit Jimbaran Using Atoll Applications - Sudiarta, Pande Ketut; Pramaita, Nyoman (Journal of Electrical, Electronics and Informatics; Vol 2 No 1 (2018): JEEI (February 2018), 2018)
Access to intranet and internet networks in the campus area requires a number of Wi-Fi devices to cover the coverage area of Udayana University. The Wi-Fi service is expected to be used for VoIP applications in the context of wireless communications. The IEEE 802.11g standard specifies an outdoor service range of 140 m and an indoor service range of 38 m. From research conducted in the engineering faculty area, the quality of VoIP service uses Wi-Fi with range of 25 m. In this research, the design of Udayana University campus Wi-Fi needs using Atoll application with IEEE802.11g standard at 140 m, 38m and 25m ranges. The results obtained to cover Udayana University campus area require Wi-Fis: 7 units for range 140 m, 98 units for range of 38 m and 225 units for range of 25 m